Synthesis and characterization of latex nanoparticles using a visible-light photoinitiating system in reverse micelles - Arbeloa, Ernesto Maximiliano (2015)
This work shows the feasibility of using the photoinitiating system composed by the xanthene dye Eosin-Y and triethanolamine on the polymerization of acrylamide in benzyl-hexadecyl-dimethylammonium chloride (BHDC) reverse micelles. Molecular weights of polyacrylamide (MWPAA) in the order of 105 and conversions up to 90 % are obtained. The size of the latex particles is in the range of the nanometers (d < 50 nm). The effect of water content and concentrations of surfactant, amine, dye, and monomer on the particle size and MWPAA are examined. Only the amine and monomer concentrations affect the MWPAA. These results are interpreted on the basis of an exchange mechanism between micelles. Practically no effect on hydrodynamic diameters is observed when the value of MWPAA is doubled. This is ascribed to a supercoiled structure of PAA inside of micelles. Our results also suggest that the polymer properties can be modulated by appropriate combination of the dye/surfactant electrical charges.